IMPACT OF SERVICE-LEARNING IMMERSION ACTIVITIES ON THE PERSPECTIVE TRANSFORMATION OF SHS STUDENTS: AN INSIDERS LENS - Therese D. San Juan, Frances; Kristopier D. Angeles, Juan (LP2M Universitas Bina Mandiri Gorontalo, 2023)
The implementation of the K-12 Curriculum in 2016 is the most significant transformation in the Philippine educational system in the postcolonial era. Along with this change of curriculum is the supplemental two years (Grade 11 and Grade 11) to the former 11-year basic education system in the country. One of the academic strands in the K-12 curriculum is the Humanities and Social Sciences which includes subjects that require service-learning immersion activities that promote transformative learning. In recent years, transformative learning has been utilized by researchers in explaining adult learning. Transformative learning has been regarded as a